ANALISIS TINGKAT KEPUASAN NELAYAN TERHADAP PELAYANAN TPI DI KECAMATAN PUGER KABUPATEN JEMBER - Rohim, Abdur; Prayuginingsih, Henik; Ridho, Atkok Ainur (Fakultas Ekonomi dan Bisnis, 2022)
Fishermen are people who actively work in fishing operations. In its operation, it is necessary to prioritize fulfilling the satisfaction of fishing communities who use TPI through good facilities andservices. Based on this, the research objectives are (1) What are the characteristics of fishermen in TPI, Puger District, Jember Regency. (2) What is the level of satisfaction of fishermen with TPI services in Puger District, Jember Regency. The research uses analytical descriptive analysis methods. The sample was determined using the quota sampling method, a total of 50 people, consisting of 25 ABK fishermen and 25 non-ABK fishermen. The data was analyzed to determine the level of user satisfaction on a scale of number 1 as the lowest value and number 5. The results of the study showed that: (1) the characteristics of fishermen with crew members at TPI Puger were an average age of 34.24 years and non-ABK fishermen aged 32.8 years were classified as productive workers. . The formal education level of fishermen with crew members has an average of 7.8, equivalent to junior high school, and non-ABK fishermen have an average of 7.32, equivalent to junior high school. The average sea experience of fishermen with crew members is 16.64 years, while the sea experience of non-ABK fishermen is 14.84 years, so it can be said that they are very experienced and already know what to do when going to sea. (2) the level of satisfaction of fishermen with crew members is 2.20 and non-ABK fishermen is 2.12. It can be concluded that overall fishermen with crew members and non-ABK fishermen are dissatisfied with TPI's services because the score is in the dissatisfied category.